Non-typhoidal salmonella colonization in chickens and humans in the Mekong delta of Vietnam - Trung, N; Carrique-Mas, J; Nghia, N; Tu, L; Mai, H; Tuyen, H; Campbell, J; Nhung, N; Nhung, H; Minh, P; Chieu, T; Hieu, T; et al. (Wiley, 2016)
Salmonellosis is a public health concern in both the developed and developing countries. Although the majority of human non-typhoidal Salmonella enterica (NTS) cases are the result of foodborne infections or person-to-person transmission, NTS infections may also be acquired by environmental and occupational exposure to animals. While a considerable number of studies have investigated the presence of NTS in farm animals and meat/carcasses, very few studies have investigated the risk of NTS colonization in humans as a result of direct animal exposure. We investigated asymptomatic NTS colonization in 204 backyard chicken farms, 204 farmers and 306 matched individuals not exposed to chicken farming, in southern Vietnam. Pooled chicken faeces, collected using boot or handheld swabs on backyard chicken farms, and rectal swabs from human participants were tested. NTS colonization prevalence was 45.6%, 4.4% and 2.6% for chicken farms, farmers and unexposed individuals, respectively. Our study observed a higher prevalence of NTS colonization among chicken farmers (4.4%) compared with age-, sex- and location- matched rural and urban individuals not exposed to chickens (2.9% and 2.0%). A total of 164 chicken NTS strains and 17 human NTS strains were isolated, and 28 serovars were identified. Salmonella Weltevreden was the predominant serovar in both chickens and humans. NTS isolates showed resistance (20-40%) against tetracycline, chloramphenicol, sulfamethoxazole-trimethoprim and ampicillin. Our study reflects the epidemiology of NTS colonization in chickens and humans in the Mekong delta of Vietnam and emphasizes the need of larger, preferably longitudinal studies to study the transmission dynamics of NTS between and within animal and human host populations.